Past Gaming Experience and Cognition as Selective Predictors of Novel Game Learning Across Different Gaming Genres - Smith, Evan T.; Bhaskar, Bhargavi; Hinerman, Alex; Basak, Chandramallika (Frontiers in Psychology, 2020)
Past experience with video games and cognitive abilities have been hypothesized to independently facilitate a greater ability to learn new video games and other complex tasks. The present study was conducted to examine this “learning to learn” hypothesis. We examined the predictive effects of gaming habits (e.g., self-identification as a “gamer,” hours spent gaming per week, weekly gaming frequency, relative preference for strategy over action games) and cognitive abilities (short-term memory, working memory, and processing speed) on learning of two novel video games in 107 participants (aged 18–77 years). One video game was from the action genre, and the other was from the strategy genre. Hours spent gaming per week and working memory were found to specifically predict learning of the novel strategy video game, after controlling for the effects of age, gender, and action game learning. In contrast, self-identification as a “gamer” was the only specific significant predictor of action game learning, after controlling for the effects of age, gender, and strategy game learning. Age of the participant negatively impacted learning of both games; however, the pattern of the predictive relationships on both action and strategy game learning was not moderated by age. Importantly, a preference for the action versus the strategy game genre had no differential effects on learning of the two novel games, nor were there any gender differences in identification as a gamer or genre preference. Findings from this study suggest that while past gaming experience and cognition do appear to influence the learning of novel video games, these effects are selective to the game genre studied and are not as broad as the “learning to learn” model suggests.